The Development of STEAM-Based LKPD - PjBL Acid-Base Solution Material to Improve Creative Thinking Ability - Abdul Hamid; Nana Nana; Syahmani Syahmani; Rusmansyah Rusmansyah (University of Muhammadiyah Malang, 2024)
This study aims to determine the validity, practicality, and effectiveness of STEAM–PjBL-based LKPD products. The research method used is research and development (R&D) with the ADDIE development model. The developed LKPD was tested on 24 class XI IPA 2 MAN 1 Banjarmasin students. The results showed that the LKPD developed was included in the very valid category in the aspects of content, presentation, language, and design assessment, with an average score of 95.5%. The LKPD that was developed also fulfilled practicality aspects with very practical categories on individual readability tests, small group readability tests, student response questionnaires, and teacher responses, as well as observation sheets on teacher abilities in managing classes. LKPD has also fulfilled the aspect of effectiveness, as seen from the results of the average N-gain percentage of 76%. So that students' creative thinking skills are included in the high category. The results of this study indicate that the product developed, namely the STEAM-PjBL-based LKPD, has met the aspects of validity, practicality, and effectiveness.